2018
DOI: 10.1007/s12264-018-0249-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Research on Alzheimer’s Disease: Progress and Perspectives

Abstract: Alzheimer's disease (AD), the most common type of dementia, is becoming a major challenge for global health and social care. However, the current understanding of AD pathogenesis is limited, and no early diagnosis and disease-modifying therapy are currently available. During the past year, significant progress has been made in clinical research on the diagnosis, prevention, and treatment of AD. In this review, we summarize the latest achievements, including diagnostic biomarkers, polygenic hazard score, amyloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 52 publications
0
79
0
6
Order By: Relevance
“…; Sun et al. ; Vina & Sanz‐Ros ). One of the most important reasons for these unsuccessful trials may have been the timing: most trials were focused on people already suffering from clinically evident dementia, where brain damage is in more advanced stages (Sun et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Sun et al. ; Vina & Sanz‐Ros ). One of the most important reasons for these unsuccessful trials may have been the timing: most trials were focused on people already suffering from clinically evident dementia, where brain damage is in more advanced stages (Sun et al.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important reasons for these unsuccessful trials may have been the timing: most trials were focused on people already suffering from clinically evident dementia, where brain damage is in more advanced stages (Sun et al. ; Vina & Sanz‐Ros ). As reversing neuronal damage may be impossible, it may be more effective to start treatment before the onset of dementia (Kumar et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the research areas supported is biomarker research, aiming at measuring diseaserelated bodily parameters. While AD biomarkers are still far from standard clinical tools, the expectation put forward by funding agencies and involved researchers is that, at some point, they will be widely available and significantly improve, first of all, diagnostic certainty and precision and, further, contribute to prediction, improved prognosis, and development of drugs (Jack et al 2011;Sun et al 2018). Tau PET is one such envisioned biomarker for AD.…”
Section: Tau Pet Imaging As Emergent Tool For Ad Diagnosis and Prognosismentioning
confidence: 99%
“…Moreover photo-active chlorin 6 dye was also found to reduce the aggregation by modulating the histidine residues (Leshem et al 2019). Methylene blue derived Leuco-methylthioninium Bis (Hydromehanesulphonate) (LMTM) entered phase-3 clinical trial for treatment of mild Alzheimer's disease (Wilcock et al 2018), however LMTM in further studies was found to be ineffective (Sun et al 2018). Toluidine Blue (TB) is a basic phenothiazine dye having structural similarity with methylene blue.…”
Section: Introductionmentioning
confidence: 99%